1991
DOI: 10.1007/bf01106105
|View full text |Cite
|
Sign up to set email alerts
|

Stratum corneum lipid abnormalities in atopic dermatitis

Abstract: Patients with atopic dermatitis (AD) often present with a dry skin. To clarify the relationship between dry skin and lipid abnormalities within stratum corneum, stratum corneum lipids were collected from six AD patients aged 15 to 25 years and from sex- and age-matched controls. All major stratum corneum lipid classes were separated and quantitated by high-performance thin-layer chromatography/photodensitometry. Six ceramide fractions were also isolated and quantitated by thin-layer chromatography/photodensito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
179
3
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(192 citation statements)
references
References 31 publications
9
179
3
1
Order By: Relevance
“…The main skin surface lipids are triglycerides, squalene, wax esters, cholesterol, ceramides, and free fatty acids (3). Although the lipid composition in AD patients is generally not different from that of healthy subjects, a significant decrease in ceramide 1 and differences in the concentrations of the related linoleate and oleate molecules have been reported (7,24). Such differences in composition might affect colonization by Malassezia strains with different lipid requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The main skin surface lipids are triglycerides, squalene, wax esters, cholesterol, ceramides, and free fatty acids (3). Although the lipid composition in AD patients is generally not different from that of healthy subjects, a significant decrease in ceramide 1 and differences in the concentrations of the related linoleate and oleate molecules have been reported (7,24). Such differences in composition might affect colonization by Malassezia strains with different lipid requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al 41 observed that the relative amounts of all the stratum corneum lipid classes including squalene, cholesterol esters, wax esters, triglycerides, free fatty acids, cholesterol, ceramides, cholesterol sulphate and phospholipids did not differ statistically between AD patients and controls but, a significant decrease in proportion of ceramide 1. On the other hand, the fatty acid compositions as well as the proportions of C16:1 straight-chain component in sebum wax esters of AD patients were very similar to those of controls.…”
Section: Discussionmentioning
confidence: 99%
“…Sebum is a growth medium for skin microorganisms and consists of squalene, cholesterol esters, wax esters, triglycerides, free fatty acids, cholesterol, ceramides, cholesterol sulfate, and phospholipids. Of these, the proportion of ceramide 1, which is a carrier of linoleate and responsible for the water-barrier function of the skin, is significantly lower in patients with AD (Yamamoto et al 1991). Therefore, the composition of sebum may also affect the fungal microbiota.…”
Section: Malassezia Colonization and Severity Of Admentioning
confidence: 99%